Does the Human Development Index relate with acute lymphoblastic leukemia incidence? - Marta M. Zapata-Tarrés; Liliana Velasco-Hidalgo; Alejandro González-Garay; Rocío Cárdenas-Cardos; Roberto Rivera-Luna (Permanyer, 2021)
Background: The association between childhood cancer and socioeconomic status has been widely studied. However, none of the results are conclusive. This study aimed to analyze the association between the Human Development Index (HDI) and the acute lymphoblastic leukemia (ALL) incidence in children under the Popular Medical Insurance Care. Methods: We conducted an observational, descriptive, and population-based study covering 55% of the Mexican population (58 million). Results: The most impoverished states were located in the south east region of Mexico, while the north was more homogeneous, with HDIs varying between 0.73 and 0.79. Our findings emphasize that the metropolitan area of Mexico City and the State of Nuevo Leon have the highest levels of HDI. Regions were graded from I to IV according to their HDIs in ascending order. The HDIs varied from 0.667 to 0.830/100,000 children/year, with a national average of 0.746. The leukemia incidence for regions I, II, III, and IV was 6.12, 6.53, 4.96, and 9.95. An analysis of ALL incidence in Mexico showed significant differences for region IV in comparison with the other regions based on the HDI values (p = 0.0001). Conclusions: Further in-depth studies, including the economic aspects of the different geographic regions and their ethnographic characteristics, would give a more comprehensive panorama.